The Application of All-Aluminum Electrical System in Wind Power - Wei, Liu; Zanbin, Wang; Wei, Zhang (New Energy Exploitation and Application, 2025)
The purpose of this paper is to explore the application of an all-aluminum electrical system in the field of wind power. Driven by the global “dual carbon” goal, the wind power industry is developing rapidly as a key force in clean energy. In view of the lightweight, high strength, corrosion resistance and good conductivity of aluminum, this paper proposes an innovative all-aluminum electrical system solution, which applies aluminum to key components such as generators, cables, transformers and converter busbars to reduce the levelized cost of energy (LCOE) and enhance market competitiveness. In this paper, through in-depth research on the mechanical and electrical properties, connection technology and short-circuit tolerance of aluminum materials, the key technologies and innovation points of the core electrical components of the all-aluminum electrical system are comprehensively analyzed, and the product application market is planned in depth. The proposed system shows 30-year lifecycle viability through accelerated aging tests, outperforming conventional materials in total ownership cost metrics. These technical advancements position aluminum electrical systems as transformative solutions for next-generation wind farms, aligning with global decarbonization objectives while addressing industry pain points in cost containment and operational reliability across diverse geographical markets.The results show that the all-aluminum electrical system has established a leading technical position in the wind power industry, and its superior LCOE perfectly meets the needs of various wind power markets, showing broad application potential and prospects.